2020
DOI: 10.1007/s10853-020-05158-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen separation from air by the combined temperature swing and pressure swing processes using oxygen storage materials Y1−x(Tb/Ce)xMnO3+δ

Abstract: Hexagonal Y1−xRxMnO3+δ (R: other than Y rare earth elements) oxides have been recently introduced as promising oxygen storage materials that can be utilized in the temperature swing processes for the oxygen separation and air enrichment. In the present work, the average and local structures of Tb- and Ce-substituted Y0.7Tb0.15Ce0.15MnO3+δ and Y0.6Tb0.2Ce0.2MnO3+δ materials were studied, and their oxygen storage-related properties have been evaluated. The fully oxidized samples show the presence of a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
(47 reference statements)
3
15
0
Order By: Relevance
“…The results indicated that the low-temperature sample possessed excellent reversibility and structural stability in oxygen absorption/desorption up to 10 cycles. In addition, a temperature swing adsorption process was also performed to investigate the oxygen storage/release performance . The sample is heated to 500 °C under a nitrogen atmosphere and then cooled to 220 °C in O 2 gas flow maintained for 20 min, subsequently heated to 360 °C in N 2 gas flow maintained for 30 min for five cycles, as presented in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the low-temperature sample possessed excellent reversibility and structural stability in oxygen absorption/desorption up to 10 cycles. In addition, a temperature swing adsorption process was also performed to investigate the oxygen storage/release performance . The sample is heated to 500 °C under a nitrogen atmosphere and then cooled to 220 °C in O 2 gas flow maintained for 20 min, subsequently heated to 360 °C in N 2 gas flow maintained for 30 min for five cycles, as presented in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…In O-PSA, gaseous oxygen is separated with the use of materials capable of absorbing oxygen only. Oxygen storage materials (OSMs) have attracted attention as absorbents used therein. …”
Section: Introductionmentioning
confidence: 99%
“…Perovskite‐based ABO 3 oxygen carriers have garnered much attention in the past decade for their rapid kinetics and resilience during repeated uptake/release cycling due to the limited structural rearrangement that occurs during oxygen gain/loss [1–24] . The efficacy of a perovskite oxygen carrier is dependent upon the identity of both the A‐ and B‐site elements chosen, with common options of Ba, Sr, Ca, and La on the A‐site, and Fe, Co, and Mn on the B‐site [1–8] .…”
Section: Introductionmentioning
confidence: 99%